Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd008497.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain and cortical stimulation for epilepsy

Abstract: Background Despite optimal medical treatment, including epilepsy surgery, many epilepsy patients have uncontrolled seizures. In the last decades, interest has grown in invasive intracranial neurostimulation as a treatment for these patients. Intracranial stimulation includes both deep brain stimulation (DBS) (stimulation through depth electrodes) and cortical stimulation (subdural electrodes). Objectives To assess the efficacy, safety and tolerability of deep brain and cortical stimulation for refractory epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 58 publications
3
70
0
5
Order By: Relevance
“…European Conformity marking) and U.S. Food and Drug Administration (FDA) approval for refractory epilepsy, respectively. 155 Transcutaneous and noninvasive VNS (tVNS, nVNS), trigeminal nerve stimulation (TNS), transcranial magnetic stimulation (TMS), and transcranial direct current stimulation (tDCS) are investigational noninvasive neurostimulation modalities. Their mechanisms of action, optimal stimulation parameters, and candidate selection criteria are currently uncertain.…”
Section: Neurostimulationmentioning
confidence: 99%
“…European Conformity marking) and U.S. Food and Drug Administration (FDA) approval for refractory epilepsy, respectively. 155 Transcutaneous and noninvasive VNS (tVNS, nVNS), trigeminal nerve stimulation (TNS), transcranial magnetic stimulation (TMS), and transcranial direct current stimulation (tDCS) are investigational noninvasive neurostimulation modalities. Their mechanisms of action, optimal stimulation parameters, and candidate selection criteria are currently uncertain.…”
Section: Neurostimulationmentioning
confidence: 99%
“…37 A recent Cochrane review notes that the sudden unexpected death in epilepsy (SUDEP) rate with RNS needs to be monitored carefully because the rate (11.8 per 1,000 patient-years) was higher than that seen in the literature for refractory epilepsy (2.2-10 per 1,000 patient-years). 38 In a similar Cochrane review for dietary treatments, there were no reports of SUDEP as an adverse effect. 39 RNS is currently available only to adult patients with focal onset epilepsy, only a limited number of epilepsy centers in the United States offer it, few neurosurgeons are familiar with implantation of the device, few epilepsy experts are trained in titrating treatment, and it is not yet available internationally.…”
Section: Responsive Neurostimulation (Rns)mentioning
confidence: 99%
“…It has been generally accepted that a transient implant effect becomes evident within 4-8 weeks after electrode implantation. 2,11 Here, the 5-month delay of NAC stimulation argues for an anti-ictal effect of the electrical stimulation rather than being a consequence of electrode insertion.…”
Section: Discussionmentioning
confidence: 92%
“…1 For these patients, neuromodulative treatment strategies may be promising. 2 First results of randomized controlled trials have demonstrated efficacy of anterior thalamic nucleus (ANT) stimulation, especially in patients with complex partial seizures and temporal lobe epilepsy. 3 Based on the data of this study, the approval of ANT stimulation in patients with refractory partial epilepsy has been granted by the European regulatory authorities.…”
mentioning
confidence: 99%